Fertility benefits of controlled ovarian stimulation and intrauterine insemination in different stages of endometriosis in a fertility centre in Southern India: a retrospective study - Sebastian, Nikhil; Radhakrishnan, Abhishek (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: To determine the fertility benefit of controlled ovarian hyperstimulation and intra uterine insemination (IUI) in different stages of Endometriosis. It was a retrospective observational study done in Kinder women’s hospital and fertility centre, Cherthala, Kerala, India. Methods: A retrospective analysis of 100 patients with isolated endometriosis (I and II vs. III and IV) who underwent IUI between January 2018 to December 2019 were selected. Cycle fecundity rates and clinical pregnancy rates and pregnancies above 28 weeks were measured. Clinical pregnancy rates with COH and IUI were also compared between grade I/II vs III/IV endometriosis. Results: A total of 16 (16%) pregnancy were achieved with controlled ovarian hyperstimulation (COH) and IUI in patients with endometriosis which included 11 (11%) clinical pregnancies and 5 (5%) miscarriages. 10% clinical pregnancies were achieved in grade I/II endometriosis and 1% in grade III/IV endometriosis. 68.75% of the pregnant patients progressed to pregnancy of >28 weeks. Conclusions: The grade of endometriosis affected the clinical pregnancy rate in COH with IUI. The treatment success of COH with IUI was noted to be greater in minimum or mild endometriosis i.e., grade I/II. The treatment modality is ineffective in moderate to severe grades of endometriosis i.e., III/IV.